PENATAAN KOLAM RETENSI SEBAGAI TAMAN KOTA DENGAN KONSEP INTEGRASI INFRASTRUKTUR DAN TAMAN AKTIF (STUDI KASUS: TANDON LENGKONG, TANGERANG SELATAN) - Rianti Alda Lestari; Suryono Herlambang; B. Irwan Wipranata (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The Lengkong reservoir consists of two reservoirs which are divided into two areas, so they are called Tandon Lengkong Wetan and Tandon Lengkong Karya. The reservoir is a water infrastructure that functions as a conservation of water resources and flood control by collecting water from housing activities to be flowed to Angke River. To take advantage of the function of the reservoir in addition to only being a water infrastructure, construction was carried out in the reservoir area to be used as a city park so that it could be used by residents as a place for recreation and exercise. To become a city park, several facilities are needed to support the needs of visitors, but in the existing conditions the existing facilities in Tandon Lengkong Wetan and Karya are still very limited and do not have an optimal arrangement and integrate between the two both physically and functionally. The purpose of this study is to identify the physical characteristics and existing conditions of infrastructure from Tandon Lengkong Wetan and Karya by involving visitor participation to provide proposals for the addition of complementary infrastructure and proposed master plans for arrangement with the concept of green infrastructure. The results of this study are in the form of a conclusion and proposed structuring master plan that divides the object of study into three zones, namely conservation zones, transition zones, and active zones where there are several concepts applied, namely the concept of flood control and water filters, the concept of conservation, the concept of sports, the concept of recreation, and the concept of supporting facilities. Keywords:  Planning; Retention Pond; Tandon Lengkong; Urban Park; Water Infrastructure Abstrak Tandon Lengkong terdiri dari dua buah tandon yang terbagi ke dalam dua wilayah sehingga disebut sebagai Tandon Lengkong Wetan dan Tandon Lengkong Karya. Tandon tersebut merupakan sebuah infrastruktur air yang berfungsi sebagai konservasi sumber daya air serta pengendali banjir dengan menampung air dari hasil aktivitas perumahan untuk selanjutnya dialirkan ke Kali Angke. Agar dapat memanfaatkan fungsi tandon selain hanya menjadi infrastruktur air, maka dilakukan pembangunan pada kawasan tandon untuk dijadikan sebagai taman kota agar dapat dimanfaatkan oleh warga sebagai tempat berekreasi dan berolahraga. Untuk menjadi sebuah taman kota dibutuhkan beberapa fasilitas guna menunjang kebutuhan para pengunjung, namun pada kondisi eksistingnya fasilitas yang ada pada Tandon Lengkong Wetan dan Tandon Lengkong Karya masih sangat terbatas serta belum memiliki penataan yang optimal dan mengintegrasikan antar keduanya baik secara fisik maupun fungsi. Tujuan dari dilakukannya penelitian ini adalah untuk mengidentifikasi karakteristik fisik dan kondisi eksisting sarana prasarana dari Tandon Lengkong Wetan dan Tandon Lengkong Karya dengan melibatkan partisipasi pengunjung untuk memberikan usulan penambahan sarana prasarana pelengkap serta usulan masterplan penataan dengan konsep infrastruktur hijau. Hasil dari penelitian ini berupa sebuah kesimpulan dan usulan masterplan penataan yang membagi objek studi menjadi tiga zona, yaitu zona konservasi, zona transisi, dan zona aktif dimana terdapat beberapa konsep yang diterapkan, yaitu konsep pengendali banjir dan penyaring air, konsep konservasi, konsep olahraga, konsep rekreasi, dan konsep fasilitas pendukung.